Toward an evolutionary theory of production - Sidney G. Winter (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2001)
Production theory in the neoclassical tradition is strong on Abstract generality. Its high level of Abstraction tends to impede understanding of technological change, partly because its perspective on production differs so much from those of engineers, managers and technologists. A more grounded approach is needed for evolutionary economics, since evolutionary thinking sees questions of production as tightly and reciprocally connected with questions of coordination, incentives, and organizational knowledge, and is concerned above all with change. In this essay, the shortcomings of mainstream theory are identified and explained in a review of its historical development. The remainder of the paper sets forth a map for a production theory that reflects the key attributes of the productive knowledge. A discussion of spatial replication of productive activity provides a sharp contrast between the evolutionary and mainstream perspectives. The paper concludes with a discussion that places production theory within the broader framework of evolutionary economics and identifies some of the many research tasks on the agenda.
Keywords: 330; Produktionstheorie; Evolutionsökonomik